2016
DOI: 10.1002/jrs.4923
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Raman spectra of brushite (CaHPO4.2H2O) crystal. Investigation of the phosphate stretching modes, study of the LOTO splitting

Abstract: Polarized Raman measurements were recorded on a monoclinic brushite (CaHPO 4 .2H 2 O) crystal in the 800-1200 cm À1 spectral range, corresponding to the P-O stretching modes. This study is a continuation of the investigation of the phosphate stretching modes observed in polarized infrared reflectance spectra of brushite crystal. In such ionic non-centrosymmetric crystals, the splitting between the transverse and longitudinal components of the optic vibrations was observed in the polarized Raman spectra recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The Raman spectra of CaP1 shows the most intense band of ν 1 PO 4 vibration, which is shifted towards a higher wavenumber (986 cm −1 ), and smaller bands appear at 1130, 1082, 1089, and 880 cm −1 . These bands are typical of brushite (CaHPO 4 •2H 2 O) [46]. For the CaP2 sample, the IR spectrum indicated Ca pyrophosphate phase, and its Raman spectrum is quite different from those of hydroxyapatites.…”
Section: Ft-ir and Raman Characterisation Of Cap Powdersmentioning
confidence: 96%
“…The Raman spectra of CaP1 shows the most intense band of ν 1 PO 4 vibration, which is shifted towards a higher wavenumber (986 cm −1 ), and smaller bands appear at 1130, 1082, 1089, and 880 cm −1 . These bands are typical of brushite (CaHPO 4 •2H 2 O) [46]. For the CaP2 sample, the IR spectrum indicated Ca pyrophosphate phase, and its Raman spectrum is quite different from those of hydroxyapatites.…”
Section: Ft-ir and Raman Characterisation Of Cap Powdersmentioning
confidence: 96%
“…Lattice dynamics has been simulated and polarization dependencies of lines intensities have been analyzed to interpret experimental Raman spectra and to attribute lines to the spectra of monoclinic and orthorhombic phases . Quillard and co‐workers have measured the polarized Raman spectra of brushite (CaHPO 4 .2H 2 O) crystal in order to investigate the phosphate stretching modes and study of the longitudinal and transverse optical phonon splitting . Wang et al reported the temperature‐dependent Raman spectra of microstructure present in dipotassium molybdate crystals and their melts.…”
Section: Solid‐state Studiesmentioning
confidence: 99%
“…[137] Quillard and co-workers have measured the polarized Raman spectra of brushite (CaHPO 4 .2H 2 O) crystal in order to investigate the phosphate stretching modes and study of the longitudinal and transverse optical phonon splitting. [138] Wang et al reported the temperature-dependent Raman spectra of microstructure present in dipotassium molybdate crystals and their melts. The mechanisms of the microstructural evolution of K 2 Mo n O 3n + 1 (n = 1, 2, 3) crystals while being melted were schematically illustrated.…”
Section: Single Crystalsmentioning
confidence: 99%